The companion cell-specific arabidopsis disaccharide carrier atSUC2 is expressed in nematode-induced syncytia - Scholz-Starke, Joachim; Sauer, Norbert; et al. (Plant Physiology, 2003)
Cyst nematodes induce a metabolically highly active syncytial cell complex in host roots. The syncytia are symplastically isolated. Because they form a strong sink, assimilates must be imported via the apoplast, thus suggesting that specific membrane-bound sugar transport proteins are expressed and activated. To identify possible candidate genes, transgenic Arabidopsis plants expressing different reporter genes under the control of different promoters from Arabidopsis sugar transporter genes were infected with the beet cyst nematode (Heterodera schachtii). With polymerase chain reaction, 13 additional sugar transporters were tested for their presence in the syncytia through the use of a syncytium-specific cDNA library. Analysis of the infected roots showed that the promoter of the sucrose (Suc) transporter AtSUC2 gene that codes for a companion cell-specific Suc transporter in noninfected plants was found to be expressed in syncytia. Its expression patterns in β-glucuronidase and green fluorescent protein plants were monitored. Syncytium-specific gene expression was confirmed by reverse transcriptase-polymerase chain reaction. Results support the idea that AtSUC2 mediates the transmembrane transfer of Suc. AtSUC2 is the first disaccharide carrier described to be activated by pathogens.